Use of modified Nilgiri bark for scavenging copper ions from industrial waste water - Charyani, Rashmi (Recent Research in Science and Technology, 2013)
<span style="font-size: 10.0pt; line-height: 115%; font-family: "Arial Narrow","sans-serif"; mso-fareast-font-family: BatangChe; mso-bidi-font-family: "Times New Roman"; mso-font-kerning: 1.0pt; mso-fareast-language: KO; mso-bidi-font-weight: bold;">Use of Nilgiri tree bark’s substract (Eucalyptus globulus) for the removal and recovery of copper ions from industrial waste water is discussed here. The dried and powdered bark is contacted with acidified formaldehyde and the resin product so obtained is found to be highly efficient in removing Cu2+ ions from the solutions. The metal ion uptake increases with increasing pH values. It is also observed that more than 99% of Cu2+ ions is removed by substrate from solutions instantaneously. By using packed columns of the substrate, the metal ion concentration from waste waters can be reduced to very low levels conforming to the acceptable water quality standards.